OPTIMIZATION OF TAX BURDEN AS A COMPOSITION OF FORMATION OF TAXABLE POLICY OF BUSINESS ENTREPRENEURS IN THE CONDITIONS OF CRISIS - Shkromyda, N.Ya. (The actual problems of regional economy development, 2018)
The article considers the necessity and methodical features of tax optimization as the main component of the tax policy of the enterprise, which is a requirement of time, especially during the period of crisis phenomena in the domestic economy. In the modern business environment, existing models of behavior of taxpayers are systematized and grouped, in particular: tax payments without the use of special measures and methods of influence on the amount of tax liabilities; tax evasion; bypassing tax payments and tax optimization. The level of tax burden has been investigated in recent years and the dynamics of its change has been analyzed. The main methods and forms of optimization of taxation of business processes of a business entity that have their advantages and disadvantages in the concrete production conditions are systematized.